Anesthetic Management of a Parturient With an Incompletely Resected Cerebral Arteriovenous Malformation. Issue 2 (March 1997) - Viscomi, Christopher M.; Wilson, James; Bernstein, Ira
Abstract : Background and Objectives: The anesthetic, neurosurgical, and obstetric literature regarding management of parturients with intracranial arteriovenous malformations is relatively sparse. A case report is given of a parturient, with a recent subtotal resection of a cerebral arteriovenous malformation, who presented for delivery of a viable male fetus. Methods: The patient was scheduled for an elective labor induction, with early epidural analgesia advocated as a strategy to minimize the cardiovascular changes of labor and prevent involuntary Valsalva maneuvers. An elective instrumental delivery was planned when the fetal head had descended appropriately. Results: Epidural analgesia was initiated when the patient reached 3 cm cervical dilation and provided excellent labor analgesia. After a passive fetal descent during the second stage of labor, Luikart-Simpson forceps were used to facilitate this stage. The newborn Apgar score was 9 at both 1 and 5 minutes after delivery. Both the patient and the infant have done well. Conclusions: The available obstetric and neurosurgical literature does not offer firm recommendations for the optimal route of fetal delivery or the timing of neurosurgical resection of an arteriovenous malformation in the parturient. Anesthetic management is predicated on the principles of minimizing the cardiovascular changes of labor and preventing involuntary Valsalva maneuvers during the second stage of labor. Both of these goals are readily accomplished with epidural anesthesia.